Vanquishers of the Crusaders: Mujāhidūn Characters in Arabic Folk Epics - Sokolov, Oleg (Religions, 2023)
Although the militant jihād remains one of the most popular topics in modern Islamic studies, most of the works focus on ideologies and actions, leaving out the popular perception of this phenomenon. Our study of the storylines about confronting the Franks (ifranj) in the Arabic folk epics, inspired by the Crusades, shows that the protagonists of the epics are presented in the narratives precisely as the holy warriors, i.e., mujāhidūn, whose key attributes are the power of faith, which often goes through tests in the fights against the infidels, as well as the divine support and readiness for martyrdom on the path of jihād. The widespread jihād and anti-Frankish rhetorics in the epics make them a valuable source for the study of the Crusades’ memory in the Medieval Arab culture.